Association of Carpal Tunnel Syndrome with Diabetic Polyneuropathy - Malik, Sayeda Shabnam; Khan, Mohammad Rezaul Karim; Hannan, MA; Alam, SK Mahbub (Journal of Enam Medical College, 2021)
Background: Common thought is that diabetic neuropathy is a predisposing factor to entrapment syndromes. Carpal tunnel syndrome (CTS) is the most frequent entrapment neuropathy. Objectives: To find out association of carpal tunnel syndrome with diabetic polyneuropathy. Materials and Methods: During the period of March 2013 to September 2015, this cross-sectional study was carried out in the Department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka. A total of 100 adult patients having symptoms and signs of polyneuropathy were recruited as study population. Of them 50 patients grouped into diabetic polyneuropathy (DPN) and the rest 50 patients in non-diabetic neuropathy due to other causes. Results: Out of all patients, the mean age was found 49.60 (13.53) years with 42% female in diabetic neuropathy patients and mean age was 44.64 (15.72) years with 46% female in non-diabetic neuropathy patients. The duration of diabetes was found 8.44 (7.79) years. According to development of Carpal tunnel syndrome (CTS), in diabetic neuropathy patients, about 58% patients developed CTS while in non-diabetic neuropathy patients, that of 14% (p=0.0001). We found diabetic neuropathy patients have 8.48 times higher possibility of development of CTS than non-diabetic neuropathy patients. On adjusted model, age as confounding variable, diabetic neuropathy and female sex were found significantly associated with development of CTS with adjusted odd ratio 10.92 and 3.78 respectfully (p<0.0001). Conclusion: In conclusion, we revealed the higher frequency of CTS in diabetics with DPN. As well we also found DPN and female sex were strongly associated with development of CTS. As DPN is a risk factor for CTS, priority should also be given to the treatment of DPN. J Enam Med Col 2021; 11(2): 78-85